Long-term acclimation to cadmium exposure reveals extensive phenotypic plasticity in Chlamydomonas. Issue 3 (16th August 2021) - Thiriet-Rupert, Stanislas; Gain, Gwenaëlle; Jadoul, Alice; Vigneron, Amandine; Bosman, Bernard; Carnol, Monique; Motte, Patrick; Cardol, Pierre; Nouet, Cécile; Hanikenne, Marc
Abstract: Increasing industrial and anthropogenic activities are producing and releasing more and more pollutants in the environment. Among them, toxic metals are one of the major threats for human health and natural ecosystems. Because photosynthetic organisms play a critical role in primary productivity and pollution management, investigating their response to metal toxicity is of major interest. Here, the green microalga Chlamydomonas ( Chlamydomonas reinhardtii ) was subjected to short (3 d) or chronic (6 months) exposure to 50 µM cadmium (Cd), and the recovery from chronic exposure was also examined. An extensive phenotypic characterization and transcriptomic analysis showed that the impact of Cd on biomass production of short-term (ST) exposed cells was almost entirely abolished by long-term (LT) acclimation. The underlying mechanisms were initiated at ST and further amplified after LT exposure resulting in a reversible equilibrium allowing biomass production similar to control condition. This included modification of cell wall-related gene expression and biofilm-like structure formation, dynamics of metal ion uptake and homeostasis, photosynthesis efficiency recovery and Cd acclimation through metal homeostasis adjustment. The contribution of the identified coordination of phosphorus and iron homeostasis (partly) mediated by the main phosphorus homeostasis regulator, Phosphate Starvation Response 1, and a basic Helix-Loop-Helix transcription factor (Cre05.g241636) was further investigated. The study reveals the highly dynamic physiological plasticity enabling algal cell growth in an extreme environment. Abstract : When chronically exposed to cadmium, a toxic metal, the green alga Chlamydomonas readjusts multiple pathways to sustain biomass production.